Characteristics and spatiotemporal changes in phenotypes and genotypes of extended-spectrum β-lactamases in Escherichia coli isolated from bloodstream infections in China from 2014 to 2021 - Sayyed Salman; Hao Xu; Yunbo Chen; Jinru Ji; Zhiying Liu; Yonghong Xiao (Annals of Clinical Microbiology and Antimicrobials)
Abstract Objective To examine the characteristics and spatiotemporal changes in the phenotypes and genotypes of extended-spectrum β-lactamases (ESBLs) in Escherichia coli strains isolated from bloodstream infections (BSIs) across China between 2014 and 2021. Methods 983 ESBL-positive E. coli strains were collected from BSIs in 66 hospitals across different geographic regions in China from 2014 to 2021. The phenotypic confirmation of ESBL was performed through the double-disc diffusion method. The genetic type was determined using polymerase chain reaction (PCR) followed by DNA sequencing. Results Between 2014 and 2021, the prevalence of ESBL-positive E. coli steadily decreased from 61.2 to 49.6%. Among 983 phenotypically confirmed ESBL-positive E. coli, 763 (77.6%) were confirmed to carry ESBL genes, with the majority being of the CTX-M type, which is further divided into 23 subtypes and dominated by the CTX-M-9 and CTX-M-1 groups, with 457/763 and 333/763, respectively. Other ESBLs and ampC genes, such as bla OXA−1, bla CMY, and bla DHA−1, often coexisted with either the CTX-M-9 or CTX-M-1 groups. bla CTX−M−14 (34.3%, 157/457) and bla CTX−M−55 (45.9%, 153/333) were the dominant subtypes in the CTX-M-9 and CTX-M-1 groups, respectively. A notable increase in bla CTX−M−27 was observed, particularly from 2019 to 2021, with 26.4%, 23.1%, and 25.8% in all genotypes. Regarding the geographical distribution of the ESBLs, the highest rate of ESBL genetic positivity was observed in Southwest China, accounting for 84.9% (45/53), and the lowest was observed in Northeast China, with 73.2% (30/41). The abundance of the bla CTX−M−27 genotype, in particular, exhibited a notable increase in Southwest China, with 31.4% (14/45) of the strains exhibiting this genotype, followed by the CTX-M-55 genotype, with 13.6% (6/45) of the strains exhibiting this genotype. Conclusions This study demonstrated a steadily decreasing trend in the incidence of ESBLs and predominant CTX-M type ESBLs, particularly the CTX-M-9 and CTX-M-1 groups, in E. coli strains across China, a notable increase in the bla CTX−M−27 genotype and regional variations in the ESBL gene distribution were detected.